2019
DOI: 10.1002/lt.25602
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Assessment in Inpatients With Cirrhosis Can Be Improved After Training and Is Associated With Lower Readmissions

Abstract: Malnutrition is widely prevalent in cirrhosis patients, which can worsen sarcopenia, hepatic encephalopathy (HE), and overall prognosis. We aimed to define the frequency of nutritional assessments of patients with cirrhosis in retrospective and prospective (after educational training) cohorts and to evaluate prospective changes along with their effects on 90‐day readmissions. This study was conducted in 2 phases. Retrospectively, records of hospitalized patients with cirrhosis from the university and Veterans … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 27 publications
0
33
0
Order By: Relevance
“…This intake was lower in Mexican‐decompensated patients compared to Americans cohorts and could contribute towards the greater hospitalization rate through microbial change. Nutritional support, which is critical for patients with decompensated cirrhosis, is associated with better outcomes 44,45 . Therefore, these results demonstrate that encouraging animal protein intake through structured nutritional interventions and assessment may be a way forward to favourable impact gut microbiota and, in turn, hospitalizations.…”
Section: Discussionmentioning
confidence: 86%
“…This intake was lower in Mexican‐decompensated patients compared to Americans cohorts and could contribute towards the greater hospitalization rate through microbial change. Nutritional support, which is critical for patients with decompensated cirrhosis, is associated with better outcomes 44,45 . Therefore, these results demonstrate that encouraging animal protein intake through structured nutritional interventions and assessment may be a way forward to favourable impact gut microbiota and, in turn, hospitalizations.…”
Section: Discussionmentioning
confidence: 86%
“…The current study by Reuter et al demonstrated good short‐term outcomes due to early nutritional evaluation and intervention in hospitalized patients with cirrhosis, but a standardized approach for nutritional assessment is not yet available. Although this study evaluated important quality measures (LOS and 90‐day readmission rates), the costs and recruitment of staff for the rigorous employment of this strategy could be challenging.…”
mentioning
confidence: 70%
“…(5) The Liver Disease Undernutrition Screening Tool is another MST that uses oral intake, weight loss, loss of subcutaneous fat or muscle mass, volume overload, and functional status. (6) In this issue, Reuter et al (7) performed a study in 3 phases that included awareness education as an intervention to involve dietary professionals earlier in the care of hospitalized patients with cirrhosis. In the retrospective phase of the study, they collected data on the frequency of dietary referrals placed upon admission at 2 transplant centers, nutritional assessment using the RFH-NPT scoring system, length of stay (LOS), and readmission rates.…”
Section: See Article On Page 1790mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, in order to diminish protein utilization, it is recommended that these patients consume breakfast, 4–6 small meals throughout the day, and a snack consisting of complex carbohydrates and some proteins late at night . Improving the inpatient nutrition consultation rates in cirrhotic patients through education is another proven strategy that is associated with lower readmission rates in 90 days …”
Section: Protein‐calorie Malnutrition and Hepatic Encephalopathymentioning
confidence: 99%